NOMA enable network optimization scheme of mobile edge computing - Feng Shaohua; Chen Qinghua; Ouyang Zhonghui; Li Zhao (Dianzi Jishu Yingyong, 2022)
Mobile edge computing(MEC) enables an intelligent terminal to transfer part of the computing load to the edge server located in the base station subsystem to solve the problem of mass data processing in IoT network. In this paper, a resource allocation scheme of terminal to edge server is proposed by studying NOMA multi-access MEC. By NOMA transmission, the intelligent terminal can offload the computing workload to different edge servers, so as to reduce the total delay of completing the computing workload of the intelligent terminal. The goal of this scheme is to minimize the cost of the system, which takes into account the total delay of the computing workload unloaded by the terminal and the cost of using the computing resources of the edge server. The numerical results of the optimal unloading solution with a single terminal are used to verify the effectiveness of the proposed solution.